Knockdown of lncRNA ENST00000609755.1 Confers Protection Against Early oxLDL-Induced Coronary Heart Disease - Sun, Yi; Huang, Shuna; Wan, Chunyu; Ruan, Qishuang; Xie, Xiaoxu; Wei, Donghong; Li, Guobo; Lin, Shaowei; Li, Huangyuan; Wu, Siying (Frontiers in Cardiovascular Medicine, 2021)
Background: This study investigated the association between long non-coding RNAs (lncRNAs) and coronary heart disease (CHD) and further elucidated the potential biological roles of lncRNAs in CHD pathogenesis. Methods: A case-control study (590 patients and 590 controls) was conducted from February 2017 and March 2019 in Fuzhou, China. Environmental factors were investigated using questionnaires and physical examinations. Five representative lncRNAs were screened using lncRNA microarray (peripheral blood in 5 cases and 5 controls) and further verified by quantitative real-time polymerase chain reaction (peripheral blood leukocyte in 100 cases and 100 controls). Oxidized low-density lipoprotein (oxLDL) was used to induce a human coronary artery endothelial cell (HCAECs) injury model, and loss of function was used to elucidate the role of lncRNA ENST00000609755.1 (lnc-MICALL2-2) in oxLDL-induced human coronary artery endothelial cells (HCAECs) injury. Results: A total of 320 lncRNAs were found dysregulated in CHD patients (fold change> 2, p<0.05). The results of a discovery microarray, population verification and HCAEC experiments suggested the lnc-MICALL2-2 is upregulated in CHD subjects and in an oxLDL-induced HCAECs injury model. Conversely, lnc-MICALL2-2 inhibition in vitro attenuated the effects of oxLDL on HCAECs morphology, proliferation, and apoptosis. Conclusion: Elevated expression of lnc-MICALL2-2 is an independent risk factor for CHD, and knockdown subsequently confers protection against early pathological processes of oxLDL-induced CHD.